Chemical composition and antibacterial and antioxidant activity of a citrus essential oil and its fractions - Ambrosio, Carmen M.S. (2021)
ABSTRACT Essential oils (EOs) from Citrus are the main by-product of Citrus-processing industries. In addition to food/beverage and cosmetic applications, citrus EOs could also potentially be used as an alternative to antibiotics in food-producing animals. A commercial citrus EO—Brazilian Orange Terpenes (BOT)—was fractionated by vacuum fractional distillation to separate BOT into various fractions: F1, F2, F3, and F4. Next, the chemical composition and biological activities of BOT and its fractions were characterized. Results showed the three first fractions had a high relative amount of limonene (≥10.86), even higher than the whole BOT. Conversely, F4 presented a larger relative amount of BOT’s minor compounds (carvone, cis-carveol, trans-carveol, cis-p-Mentha-2,8-dien-1-ol, and trans-p-Mentha-2,8-dien-1-ol) and a very low relative amount of limonene (0.08–0.13). Antibacterial activity results showed F4 was the only fraction exhibiting this activity, which was selective and higher activity on a pathogenic bacterium (E. coli) than on a beneficial bacterium (Lactobacillus sp.). However, F4 activity was lower than BOT. Similarly, F4 displayed the highest antioxidant activity among fractions (equivalent to BOT). These results indicated that probably those minor compounds that detected in F4 would be more involved in conferring the biological activities for this fraction and consequently for the whole BOT, instead of the major compound, limonene, playing this role exclusively.